Analyses of hypoxia-related risk factors and clinical relevance in breast cancer - Li, Yan; Yu, Haiyang; Han, Xinghua; Pan, Yueyin (Frontiers in Oncology, 2024)
Hypoxia plays an important role in the heterogeneity, relapse, metastasis and drug resistance of breast cancer. In this study, we explored the hypoxia-related biological signatures in different subtypes of breast cancer and identified the key prognostic factors by bioinformatic methods. Based on The Cancer Genome Atlas (TCGA) Breast Cancer datasets, we divided the samples into immuneactivated/suppressed populations by single-sample gene set enrichment analysis (ssGSEA), and then used Hierarchical Clustering to further identify hypoxic/non-hypoxic populations from the immunesuppressive samples. Most of the immune checkpoint genes were highly expressed in the hypoxic group. We constructed a hypoxia-related risk model of breast cancer. Nuclear factor interleukin-3 regulated (NFIL3), serpin family E member 1 (SERPINE1), FOS, biglycan (BGN), epidermal growth factor receptor (EGFR) and sushi-repeat-containing protein, X-linked (SRPX) were identified as key hypoxia related genes. Margin status, AJCC stage, hypoxia status, ER/PR status, NFIL3, SERPINE1, EGFR and RiskScore were identified as independent prognostic indicators for breast cancer patients. The 3-and 5-year survival curves of the model and immunohistochemical staining on the breast cancer microarray verified the statistical significance and feasibility of our model. Among the different molecular types of breast cancer, ER/PR+ and HER2+ patients might have higher hypoxia-related RiskScore. ER/PR-negative samples demonstrated more activated immune-related pathways and better response to most anticancer agents. Our study revealed a novel risk model and potential feasible prognostic factors for breast cancer and might provide new perspectives for individual breast cancer treatment.a 删除[Kate Lee]: